Optimal transmission strategy of diamond channel with limited battery capacity of source node - Taoshen LI; Li SUN; Zhe WANG (Tongxin xuebao)
In order to solve the problem that the energy harvesting uncertainty of node in wireless energy harvesting network makes it difficult for the system to design a reasonable transmission strategy, a diamond channel with limited battery capacity of the source node were constructed.The goal was to maximize the end-to-end throughput of the system.Under the conditions of meeting the constraints of energy and data causality between transmission nodes and no battery energy overflow, a model to maximize the end-to-end throughput of the system was built, and an optimal offline transmission power and rate allocation strategy was proposed.Firstly, based on theoretical analysis and formula derivation, the strategy transformed the optimal transmission problem into the optimal transmission problem on the side of the broadcast channel, and used the water-filling algorithm to solve the optimal total power from the source node to the relay node.Then, the throughput of the source node to each relay node was analyzed based on the cutoff power level in the broadcast channel throughput maximization problem.Finally, according to the data arrival of the relay node, the iterative water-filling method was used to solve the optimal transmission power from the relay node to the destination node, and the optimal rate was solved by extending the optimal rate of the multiple access channel.Simulation results demonstrate the feasibility and correctness of the proposed optimization policies.